Empirical models of kinetic rate for river treatment analysis of cellulosic materials - Low, Wen-Pei; Mohd Fadhil, Md Din; Chang, Fung-Lung; Siti Nur Fatihah, Binti Moideen; Yee, Yong Lee (Elsevier Ltd., 2018)
Wen-Pei Lowa,⁎, Mohd Fadhil Md Dinb,c, Fung-Lung Changa, Siti Nur Fatihah Binti Moideend, Yee Yong Leee